Mo‐Vacancies Defect Engineering of One‐Dimensional Porous Mo2C Nanowires for Enhanced High‐Efficiency Hydrogen Evolution. Issue 11 (7th April 2022) - Nie, Zhongxiang; Tang, Zeming; Jiao, Dongxu; Yuan, MeiChen; Zhao, Jingxiang; Lai, Qingxue; Liang, Yanyu
Abstract: The large‐scale application of efficient water‐splitting greatly promote the development of hydrogen economy which benefit both in alleviating the energy crisis and reaching the goal of carbon neutral. To realize considerable hydrogen evolution, rational design of catalysts with controllable structure and surface composition become crucial. In this work, we proposed an enhanced active site originated from Mo‐vacancies defect in Mo2 C crystal which was fabricated by the evaporation of Zn content in well‐designed one‐dimensional ZnMoO4 precursor. Density functional theory calculation and experimental results demonstrated that the formation of molybdenum vacancies in molybdenum carbide promoted the water adsorption and H2 desorption effectively, resulting in an excellent HER reaction dynamics. Moreover, one‐dimensional porous nanowires also ensured rapid mass transfer and contributed strong support for superexcellence HER performance. As expected, V−Mo2 C‐900@NF exhibited extremely low overpotential ( η10 =43 mV) at the current density of 10 mA cm −2 and rapid reaction kinetics (Tafel slope 77.89 mV dec −1 ). Abstract : We proposed a novel strategy to fabricate the hierarchically porous structure along with plenty of vacancies which could not merely expose higher specific surface area and sufficient reaction sites towards HER, but also accelerate mass transport and promote adsorption and dissociation of water.